School Library Management Information System - Felia Santika; Riswanti Rini (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
The purpose of this research is to find out how the school library management information system at SMP Al Azhar 3 Bandar Lampung. The method used in this study is a descriptive qualitative method where data collection uses interview, observation, and documentation techniques. The research samples were the principal, the head of the library and the library staff. The results showed that the library of SMP Al Azhar 3 Bandar Lampung has implemented a library management information system called BAMBO MEDIA. Implementations that are carried out ranging from processing, borrowing to the process of returning books have implemented a library management information system. with the implementation of the system well, it facilitates the process of managing the library in SMP Al Azhar 3 Bandar.